In–situ XRD and EDS method study on the oxidation behaviour of Ni–Cu sulphide ore - Guangshi Li (Nature Portfolio, 2017)
Abstract The oxidation mechanism of sulfides is the key issue during the sulphide–metallurgy process. In this study, the phase transformation and element migration were clearly demonstrated by in–situ laboratory–based X–ray diffraction (XRD) and energy–dispersive X–ray spectroscopy (EDS), respectively. The reaction sequence and a four–step oxidation mechanism were proposed and identified. The elemental distribution demonstrated that at a low temperature, the Fe atoms diffused outward and the Ni/Cu atoms migrated toward the inner core, whereas the opposite diffusion processes were observed at a higher temperature. Importantly, the unique visual presentation of the oxidation behaviour provided by the combination of in–situ XRD and EDS might be useful for optimising the process parameters to improve the Ni/Cu extraction efficiency during Ni–Cu sulphide metallurgy.